The NuSTAR Serendipitous Survey : The 80 Month Catalog and Source Properties of the High-energy Emitting Active Galactic Nucleus and Quasar Population - Greenwell, Claire L. (American Astronomical Society, 2025)
We present a catalog of hard X-ray serendipitous sources detected in the first 80 months of observations by the Nuclear Spectroscopic Telescope Array (NuSTAR). The NuSTAR serendipitous survey 80 month (NSS80) catalog has an unprecedented ∼62 Ms of effective exposure time over 894 unique fields (a factor of 3 increase over the 40 month catalog, NSS40), with an areal coverage of ∼36 deg2, larger than all NuSTAR extragalactic surveys. NSS80 provides 1274 hard X-ray sources in the 3−24 keV band (822 new detections compared to the previous NSS40). Approximately 76% of the NuSTAR sources have lower-energy (<10 keV) X-ray counterparts from Chandra, XMM-Newton, and Swift-XRT. We have undertaken an extensive campaign of ground-based spectroscopic follow-up to obtain new source redshifts and classifications for 427 sources. Combining these with existing archival spectroscopy provides redshifts for 550 NSS80 sources, of which 547 are classified. The sample is primarily composed of active galactic nuclei (AGNs), detected over a large range in redshift (z = 0.012-3.43), but also includes 58 spectroscopically confirmed Galactic sources. In addition, five AGN-galaxy pairs, one dual AGN system, one BL Lac candidate, and a hotspot of 4C 74.26 (radio quasar) have been identified. The median rest-frame 10−40 keV luminosity and redshift of NSS80 are 〈L 10−40 keV〉 = 1.2 × 1044 erg s−1 and 〈z〉 = 0.56. We investigate the optical properties and construct composite optical spectra to search for subtle signatures not present in the individual spectra, finding an excess of redder BL AGNs compared to optical quasar surveys, predominantly due to the presence of the host galaxy and, at least in part, due to dust obscuration.